Wali Hakim dalam Perspektif Maslahah Mursalah (Studi Kasus terhadap Perwalian Nikah di Kabupaten Jombang) - Moh Lutfi Ridlo (Institut Agama Islam Negeri (IAIN) Kediri, 2022)
In Islam, marriage is a sacred stage and is clearly regulated religion. One of them is the presence of guardian judges in marriage, although, in its application to differences of opinion among scholars, its presence in the wedding ceremony is a must. This paper tries to describe the position of guardian judges in marriage from the perspective of maslahah mursalah by using a qualitative descriptive approach. The author tries to present the problem of marriage in the Jombang Regency area and presents data based on a theoretical framework so that a complete conclusion can be drawn. The results of this study are that in several marriage problems in Jombang Regency, the Guardian Judge is one of the solutions for the benefit of the bride whose guardian does not meet the requirements for marriage.